2020
DOI: 10.3389/fdgth.2020.00009
|View full text |Cite
|
Sign up to set email alerts
|

Health Self-Management Applications in the Work Environment: The Effects on Employee Autonomy

Abstract: Organizations increasingly use Health Self-Management Applications (HSMAs) that provide feedback information on health-related behaviors to their employees so that they can self-regulate a healthy lifestyle. Building upon Self-Determination Theory, this paper empirically investigates the basic assumption of HSMAs that their self-management feature provides employees with autonomy to self-regulate their health-related behavior. The two-phase experimental study contained a 4-weeks HSMA intervention in a healthca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The underlying assumption was that the use of digital health technologies provides workers with autonomy via feedback and the freedom to respond to self-regulate health-related behaviour. Despite adjustments to the messages, intended to limit the impact on worker autonomy, these findings revealed that the use of a sensor technology did not significantly increase perceived autonomy and may have even reduced autonomy under certain conditions, especially for less healthy workers ( 50 ). Moreover, the workers who had used an activity tracker to monitor their behaviour before they received an employer-provided device experienced the same decrease in autonomy as the workers who used the activity tracker for the first time.…”
Section: Case Studymentioning
confidence: 86%
See 4 more Smart Citations
“…The underlying assumption was that the use of digital health technologies provides workers with autonomy via feedback and the freedom to respond to self-regulate health-related behaviour. Despite adjustments to the messages, intended to limit the impact on worker autonomy, these findings revealed that the use of a sensor technology did not significantly increase perceived autonomy and may have even reduced autonomy under certain conditions, especially for less healthy workers ( 50 ). Moreover, the workers who had used an activity tracker to monitor their behaviour before they received an employer-provided device experienced the same decrease in autonomy as the workers who used the activity tracker for the first time.…”
Section: Case Studymentioning
confidence: 86%
“…The project SPRINT@Work is an EU-funded interdisciplinary project aimed at developing and evaluating sensor and intervention technologies that contribute to keeping ageing workers healthy and effectively employable (45,(50)(51)(52)(53)(54)(55)(56). These health-related technologies were developed and implemented by researchers and engineers from a variety of disciplines (cognitive neuroscience, information management, biomedical engineering and rehabilitation medicine, community and occupational medicine), in collaboration with companies.…”
Section: Practical Examples Project Descriptionmentioning
confidence: 99%
See 3 more Smart Citations